Flood Control: How Milk-Derived Extracellular Vesicles Can Help to Improve the Intestinal Barrier Function and Break the Gut–Joint Axis in Rheumatoid Arthritis - Aarts, Joyce; Boleij, Annemarie; Pieters, Bartijn C. H.; Feitsma, Anouk L.; van Neerven, R. J. Joost; ten Klooster, Jean Paul; M’Rabet, Laura; Arntz, Onno J.; Koenders, Marije I.; van de Loo, Fons A. J. (Frontiers in Immunology, 2021)
Many studies provided compelling evidence that extracellular vesicles (EVs) are involved in the regulation of the immune-response, acting as both enhancers and dampeners of the immune system, depending on the source and type of vesicle. Research, including ours, has shown anti-inflammatory effects of milk-derived EVs, using human breast milk as well as bovine colostrum and store-bought pasteurized cow milk, in in vitro systems as well as therapeutically in animal models. Although it is not completely elucidated which proteins and miRNAs within the milk-derived EVs contribute to these immunosuppressive capacities, one proposed mechanism of action of the EVs is via the modulation of the crosstalk between the (intestinal) microbiome and their host health. There is increasing awareness that the gut plays an important role in many inflammatory diseases. Enhanced intestinal leakiness, dysbiosis of the gut microbiome, and bowel inflammation are not only associated with intestinal diseases like colitis and Crohn’s disease, but also characteristic for systemic inflammatory diseases such as lupus, multiple sclerosis, and rheumatoid arthritis (RA). Strategies to target the gut and especially its microbiome are under investigation and hold a promise as a therapeutic intervention for these diseases. The use of milk-derived EVs either as stand-alone drug or using the vesicles as a drug-carrier is often suggested in recent years. Several research groups have studied the tolerance and safety of using milk-derived EVs in animal models, and the overall consensus is that they are well tolerated with only slightly induced serum cytokine levels. Due to its natural origin, milk-derived EVs are highly biocompatible and have limited immunogenicity even cross species, which gives them great advantages over traditional synthetic delivery vehicles such as liposomes. Furthermore, it has been demonstrated that milk-derived EVs, when taken up in the gastrointestinal tract, stay intact after absorption, indicating excellent stability. These characteristics make milk-derived EVs very suitable as drug carriers, but also by themselves, these EVs already have a substantial immunoregulatory function, and even without loading, these vesicles can act as therapeutics. In this review we will address the immunomodulating capacity of milk-derived EVs and discuss their potential as therapy for RA patients.